2003
DOI: 10.1037/0735-7028.34.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Leading researchers' consensus on psychotherapy research findings: Implications for the teaching and conduct of psychotherapy.

Abstract: We examined leading international psychotherapy researchers' views on psychotherapy outcome research. Participants completed a questionnaire on which they rated level of research evidence for or against various assertions about psychotherapy processes and outcomes. Participants rated how confident they were that the assertions were supported by psychotherapy research. Strong, or relatively strong, consensus was achieved on several of the questionnaire items. Areas for which relative uniformity of opinion does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
(31 reference statements)
2
16
2
1
Order By: Relevance
“…Only two studies have found no signifi cant difference between self-help programs involving telephone contact and completely self-administered programs, or a wait list condition (Mead et al, 2005;. There is also considerable data indicating that paraprofessionals can be just as effective as professionals in providing viable therapy options (Boisvert & Faust, 2003;Christensen & Jacobson, 1994;Faust & Zlotnick, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Only two studies have found no signifi cant difference between self-help programs involving telephone contact and completely self-administered programs, or a wait list condition (Mead et al, 2005;. There is also considerable data indicating that paraprofessionals can be just as effective as professionals in providing viable therapy options (Boisvert & Faust, 2003;Christensen & Jacobson, 1994;Faust & Zlotnick, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the recent interest in negative effects of psychological treatments among researchers, clinicians might not be as aware and up to date regarding the debate on how to monitor and report negative effects (Castonguay et al, 2010 ). Investigations of how clinicians perceive and experience negative effects in their clinical practice are scarce, but there are some indications that they may not acknowledge that some patients fare worse and encounter adverse events (Boisvert & Faust, 2003 ). Strupp and Hadley ( 1976 ) distributed a survey on negative effects to 150 researchers and clinicians, of whom 70 responded, with a majority agreeing that negative effects constitute a significant problem in psychological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Anaclitic individuals use predominantly avoidant defenses such as denial, repression, and displacement, in an effort to maintain interpersonal ties, because of an exaggerated and distorted emphasis on interpersonal relatedness (Blatt, 2008;Blatt & Blass, 1996). However, the development of the self is neglec-Therapeutic communication, specifically the speech of patients and therapists, is a dimension in which, microanalytically speaking, therapeutic change is constructed (Boisvert & Faust, 2003;Elliot, Slatick, & Urman, 2001;Krause, et al, 2007;Llewelyn & Hardy, 2001;Orlinsky, Ronnestad, & Willutzki, 2004;Wallerstein, 2001). However, this activity has received less attention than the effectiveness of therapy or therapeutic outcomes (Asay & Lambert, 1999;Messer & Wampold, 2002;Wampold, 2005;Wampold, Ahn, & Coleman, 2001), or unspecific or common factors such as the therapeutic alliance (Hubble, Duncan, & Miller, 1999;Krause, 2005;Maione & Chenail, 1999;Meyer, 1990;Orlinsky & Howard, 1987).…”
Section: Anaclitic and Introjective Personality Configurationsmentioning
confidence: 99%